Research in the use of artificial intelligence technology in media integration in China - Liu, Meng; Wan Abas, Wan Anita; Mamat, Roslina (Human Resource Management Academic Research Society, 2023)
This paper studies about the continues growth of national economy and innovation of science and technology the level of construction and development of China's artificial intelligence field has made a qualitative leap. The reasonable application of artificial intelligence technology is the most important and indispensable key element of the modern media integration process, which can not only maximize the role of the media in the social scope of communication functions, but also effectively give the advantages of diversified media communication, realize the real time interactive communication between the media and the market users, and comprehensively enhance the core competitiveness of mainstream media.This essay will future analyze and discuss the use of artificial intelligence technology in media convergence, aiming to provide scientific reference opinions for the same industry in China.